Estudo da Relação Quantitativa entre Estrutura e Propriedade de Compostos Triazolopirimidinícos com Atividade Herbicida sobre AHAS - Messias, Evandro (2022)
Weed resistance to herbicides has reached levels that cause significant economic damage in recent decades, considering that it is the highest number of cases of resistant biotypes found in the mechanism of action of Acetohydroxyacid synthase (AHAS) inhibitors. Persistent and intensive herbicide use in chemical control of weeds has caused selection pressure on groups of sensitive plants, allowing only resistant individuals to survive and reproduce. In most cases of resistance reported so far in research studies, resistance to AHAS inhibitors has been attributed to changes in the sequence of specific amino acids in their structure. In doing so, we highlight the importance of studying the factors that cause structural changes in AHAS that may result in the loss of herbicide affinity by taking into account the place of action on the enzyme. Thus, this thesis preconizes the interactions between AHAS of Arabidopsis thaliana (AtAHAS) and mutant (P197L) with a set of 55 molecules derived from the compound 2-aroxyl-1,2,4-triazolopyrimidine. Our aim is to generate predictive models that may help to elucidate important structural requirements for increasing the herbicidal activity concerning the class of triazole compounds. As methodology, we based our research study on Quantitative Structure-Property Relationship - QSPR through Comparative Molecular Field Analysis - CoMFA. Steric and electrostatic contour maps resulted by CoMFA model indicated the significance of certain substituent groups at specific positions on the phenyl group, which corresponds to the substituent group of the triazole ring, for the increase of biological activity. Results show the implication of the planned synthesis of triazole compounds with herbicidal activity on the AHAS enzyme.